Prolapsed Lumbar Intervertebral Disc with Lumbar Radiculopathy Management: A Comparative Evaluation of Transforaminal Epidural Steroid Injection and Lumbar Traction - Asiful Haque; Mohammed Emran; Fatema Tuz Zohora; Md Zulfikar Ali; H N Masuk Rahman (KYAMC Journal, 2025)
Background: Lumbar radiculopathy, is commonly caused by intervertebral disc herniation. Non-surgical treatments like Transforaminal Epidural Steroid Injection (TESI) and lumbar traction could be good options to alleviate pain and improve functionality. Objective: To compare the effectiveness of TESI and lumbar traction. Materials and Methods: A prospective, randomized, comparative trial conducted on 100 patients of lumbar radiculopathy due to intervertebral disc herniation confirmed by MRI, were randomly assigned to either the TESI group (n=50) or the lumbar traction group (n=50). Outcome was assessed using the Visual Analog Scale (VAS), the Oswestry Disability Index (ODI), and a five-point Likert scale. Results: In terms of pain reduction, the TESI group’s mean VAS score decreased from 7.5 at baseline to 3.2 at two weeks and 2.8 at six months, while the lumbar traction group saw a decrease from 7.6 to 5.1 at two weeks and 4.5 at six months. Similarly, in functional improvement - the ODI scores showed in the TESI group, decreasing from 50% to 24% at two weeks and 18% at six months, compared to the lumbar traction group’s from 49% to 38% at two weeks and 31% at six months. At six months in the TESI group, 85% of patients reporting being "very satisfied" or "satisfied," compared to 65% in the lumbar traction group. These indicate that TESI is more effective in reducing pain, improving function, and increasing patient satisfaction. Conclusion: The transforaminal epidural steroid injection (TESI) is significantly more effective than lumbar traction in reducing pain, improving functional outcomes, and increasing patient satisfaction.